Industrial society and rehabilitation - problems and solutions : ISRD-proceedings of the tenth world congres - Dicke, Werner; Jochheim, Kurt-Alphons; Müller, Marlis; Thom, Harald; World Congress. International Society for Rehabilitation of the Disabled 11-17/09/1966 (Heidelberg-Schlierbach : Deutsche Vereinigung für die Rehabilitation Behinderter e. V., 1966)
Verslag van een congres rond rehabilitatie dat plaats had in Wiesbaden in 1966.